Characterization of membrane vesicles released by Mycobacterium avium in response to environment mimicking the macrophage phagosome - Chiplunkar, Sanket S (Future Microbiol, 2019)
AIM: To investigate the formation of Mycobacterium avium membrane vesicles (MVs) within macrophage phagosomes. MATERIALS & METHODS: A phagosome model was utilized to characterize proteomics and lipidomics of MVs. A click chemistry-based enrichment assay was employed to examine the presence of MV proteins in the cytosol of host cells. RESULTS: Exposure to metals at concentrations present in phagosomes triggers formation of bacterial MVs. Proteomics identified several virulence factors, including enzymes involved in the cell wall synthesis, lipid and fatty acid metabolism. Some of MV proteins were also identified in the cytosol of infected macrophages. MVs harbor dsDNA. CONCLUSION: M. avium produces MVs within phagosomes. MVs carry products with potential roles in modulation of host immune defenses and intracellular survival.